The Classroom as a Metaphorical Canoe: Cooperative learning in Pacific Studies - Teaiwa, Teresia K. (WINHEC: International Journal of Indigenous Education Scholarship, 2005)
In this article I use the "canoe" as a metaphor for re-conceptualizing the university undergraduate classrooms in which I teach Pacific Studies. Thecanoe metaphor emphasizes the idea of "a journey", or a process of learning, over "the destination" or product. Given the immensity and diversity of the Pacific Islands region, with approximately 20% of the world's languages spread across islands in the world's largest body of water, it becomes absurd for any lecturer in Pacific Studies to be positioned as an authority on the region. In Pacific Studies, lecturers must be prepared to navigate into unfamiliar waters. The canoe metaphor thus also allows for a cooperative approach to learning, and fosters shared responsibility between lecturers and tutors on one hand, and students on the other. Referring to Joseph Lawman's classic text, Mastering the Technique of Teaching (1984), I review fundamental aspects of teaching practice in the light of the particular imperatives of Pacific Studies.